Pengalaman Masa Remaja Sebagai Faktor Pembentuk Kepribadian Pada Individu Dengan Bipolar Disorder - Delvita Yandika Putri; Sri Nurhayati Selian (CV. ITTC INDONESIA, 2026)
This study aims to deeply understand the experiences of adolescence as a factor in shaping the personality of individuals with Bipolar Disorder. A qualitative approach with a phenomenological design was used to explore the meaning of the participants' subjective experiences. The three participants were two women and one man who had been diagnosed with Bipolar Disorder and were university students. Data collection techniques used semi-structured in-depth interviews and field notes. Data analysis was conducted through reflexive thematic analysis with the stages of data familiarization, coding, theme formation, review, definition, and writing. Data validity was maintained through source and time triangulation and member checking. The results identified four main themes: (1) stressful family relationship dynamics, (2) peer experiences that shape social relationship patterns, (3) unmanaged emotional turmoil, and (4) the process of meaning-making and self-adaptation. Findings indicate that adolescent experiences, particularly inconsistent parenting patterns, family conflict, and peer pressure, significantly contributed to shaping the participants' personalities, making them emotionally sensitive, wary of social relationships, yet resilient in the face of adversity.